2019
DOI: 10.3390/coatings9120841
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Resistant TiTaN and TiTaAlN Thin Films Grown by Hybrid HiPIMS/DCMS Using Synchronized Pulsed Substrate Bias with No External Substrate Heating

Abstract: Ti0.92Ta0.08N and Ti0.41Al0.51Ta0.08N thin films grown on stainless-steel substrates, with no external heating, by hybrid high-power impulse and dc magnetron sputtering (HiPIMS/DCMS), were investigated for corrosion resistance. The Ta target was operated in HiPIMS mode to supply pulsed Ta-ion fluxes, while two Ti (or Ti and Al) targets were operated in DCSM mode in order to provide a high deposition rate. Corrosion resistance was investigated using potentiodynamic polarization and electrochemical impedance spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 69 publications
(127 reference statements)
0
1
0
Order By: Relevance
“…Early examples of advantages offered by a hybrid HiPIMS/DCMS technique with metal-ion-synchronized substrate bias include the use of Ta + ( m Ta = 181.0 amu) or W + HiPIMS ions ( m W = 183.8 amu) to grow dense and hard Ti 1- x-y Al x Ta y N 9 , Ti 1- x Ta x N 8 , or Ti 0.40 Al 0.27 W 0.33 N 17 films at the substrate temperatures not exceeding 150 °C. The high quality of these layers was confirmed by the application studies in which Ti 1- x Ta x N layers performed exceptionally well as Cu diffusion barriers on Si (001) 18 and provided excellent corrosion protection for stainless-steel substrates 19 . Systematic studies of densification effects induced by group VIB transition metal (TM) target ions in Ti 0.50 Al 0.50 N demonstrated that the densification effects scale with the mass of HiPIMS-generated metal-ions 20 .…”
Section: Introductionmentioning
confidence: 84%
“…Early examples of advantages offered by a hybrid HiPIMS/DCMS technique with metal-ion-synchronized substrate bias include the use of Ta + ( m Ta = 181.0 amu) or W + HiPIMS ions ( m W = 183.8 amu) to grow dense and hard Ti 1- x-y Al x Ta y N 9 , Ti 1- x Ta x N 8 , or Ti 0.40 Al 0.27 W 0.33 N 17 films at the substrate temperatures not exceeding 150 °C. The high quality of these layers was confirmed by the application studies in which Ti 1- x Ta x N layers performed exceptionally well as Cu diffusion barriers on Si (001) 18 and provided excellent corrosion protection for stainless-steel substrates 19 . Systematic studies of densification effects induced by group VIB transition metal (TM) target ions in Ti 0.50 Al 0.50 N demonstrated that the densification effects scale with the mass of HiPIMS-generated metal-ions 20 .…”
Section: Introductionmentioning
confidence: 84%